STUDI LIVING HADIS: DILIHAT DARI PERKEMBANGAN DAN METODOLOGI - Idris Siregar (SHAHIH (Jurnal Ilmu Kewahyuan), 2022)
Living hadith is interpreted more based on the existence of living traditions in society that refer to hadith and its practices according to their needs. As happened to a friend who acted not based on the Prophet's shari'a because in the course of the hadith there will undoubtedly be changes and continuities where the changes are related to the application of growing knowledge. Living sunnah and hadith are not new, only the terms just use the new one. Living hadith is a continuation of what friends and tabi'in practiced in the past. Through the development of the study of living hadith, many methods have been used in its study.